A historical study of the population and urban development of the city of Ma'an during the period 1850-1921 - Abdel Hadi Al Jaz, Mohammad; Mahmoud Al-Maani, Abd-Al Razzak (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to shed light on important aspects of urban life in the city of Ma'an during the period (1850- 1921 AD).The importance of the study lies in its documentation of the features of urban life in the city during that historical period. This study has adopted the method of analyzing documents pertaining to the history of the city, which sufficient information can be inferred from it. The population centers have been reached, as well as the development that occurred in them which increased numbers of population contributed, since the beginning of the second half of the nineteenth century. So Maan became the city that contains many population centers. Through this study, the materials used to build these houses were monitored, which were of milk and construction in relation to the walls. As for the roof, it is made of wood and tree branches, and dirt, mixed with straw, is placed over it. Some of these houses consist of two floors, water tanks, and roofed monsters. There are also Legitimacy benefits, a kitchen. Buildings were also found to be used on the zinco roof.